Design and analysis of enterprise management system framework based on blockchain - Wei ZHAO; Wenyin ZHANG; Jiuru WANG; Yawei ZHANG (网络与信息安全学报)
How to enhance the management of modern enterprises by blockchain technology has attracted more and more attention.ERP (enterprise resource planning) technology combined modern information technology with enterprise production process management,and effectively strengthened the work efficiency and management level of enterprises.But there were inherent pain points such as equipment security,data security,industrial control security,information leakage and so on.Aimed at the problems exposed by ERP system,a blockchain based framework mod el of ERP system proposed by taking advantage of the characteristics of decentralization,de-trust,openness and transparency,trusted database and traceability of blockchain.The key point is to solved the problem of credible and efficient data collaboration in the production and management process of enterprises.Combine with the incentive mechanism of blockchain,use token to strengthen collaborative management and improve efficiency,which provide a new idea for enterprise performance evaluation and assessment.